Machiavellian Principles Depicted in William Shakespeare’s Othello - Raden Ayu Qisthi Shafira Sukardi (Universitas Gadjah Mada, 2015)
This research is aimed to identify Machiavellian principles applied in Iago’s traits. Dynamic structuralism proposed by Mukarovsky is applied as its theoretical approach, so the discussion of this research evolves around the intrinsic elements of the play as well as the historical background of Machiavelli and the principles. By conducting a library research as the method, it is revealed that Machiavelli has his own idea to define power. According to Machiavelli, achieving power has to deal with virtù as a force. This is considered as the highlight of Machiavellian principles in this research.Therefore, the interaction between Iago and other characters are analyzed to see the application of Machiavellian principles in Iago’s traits. Iago’s plan is highlighted and linked to Machiavellian principles, saying that it is acceptable for someone to be harmful and selfish as the ways to achieve power. As the result, this research concludes that Iago has various personalities: as a backstabber, a trickster, and a master of exploiting other people’s mind. These personalities are aligned with Machiavellian principles. Iago manages a mischievous plan to destroy other people’s lives. His atrocious behavior represents the idea of a Machiavellian virtùe, described as a part of Machiavellian principles.